Hubungan Tingkat Stres dengan Kejadian Dismenore Primer pada Siswi SMA/MA di Makassar - Rizqi Maulidah; Azizah Nurdin; Rahadi Arie Hartoko; Fhirastika Annisa Helvian; Zulfahmi Alwi (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Dysmenorrhea is a condition experienced by women during menstruation which causes abdominal pain that interferes with activities. Based on theory, stress can increase the risk of menstrual cramps. A person experiences stress when faced with events or conditions that can harm or interfere with their ability to control them. According to WHO, dysmenorrhea is experienced by 50% of adolescents in every country. This study aims to examine the relationship between stress levels and the incidence of primary dysmenorrhea in female high school students in Makassar. The method used was cross-sectional, with 348 samples selected by purposive sampling. The research measuring tools used were questionnaires: Perceived Stress Scale (PSS) and Visual Analog Scale (VAS). The research results showed that the majority of samples experienced moderate stress 291 samples (83.6%), moderate dysmenorrhea 211 samples (60.6%), and 176 samples (50.6%) experienced moderate dysmenorrhea with moderate stress. When processing the data using the chi-square test, it was found that p-value=0.005 (p<0.05). This study concludes that there is a relationship between stress levels and the occurrence of primary dysmenorrhea among high school students in Makassar.